Thermodynamic investigation of the Zr-Fe-Nb system and its applications. (September 2017) - Lu, Hai-Jin; Zou, Nan; Zhao, Xu-Shan; Shen, Jian-Yun; Lu, Xiao-Gang; He, Yan-Lin
Abstract: The total energies and enthalpies of intermetallic compounds, such as the Laves phases, Fe23 Zr6 and τ1, in the Zr-Fe-Nb system have been studied by using the first-principles pseudo-potential VASP code with a full relaxation of all structural parameters. Based on the calculation results and recent experimental information, a new thermodynamic description of the Fe-Zr binary system has been established using the CALPHAD approach. The controversial intermetallic phase Fe23 Zr6 in the Fe-Zr system was treated as a stable phase and the high-temperature Laves C36 phase was excluded from equilibrium. However, the first-principles calculations show that the Fe23 Zr6 phase is not stable at 0 K implying a transition from metastable to stable Fe23 Zr6 at certain temperature, i.e. 225 K predicted by the present work. The thermodynamic description of Fe-Nb system has been revised to better fit the experimental data for the Laves C14 phase boundary. The thermodynamic description of the Zr-Fe-Nb system has been developed based on the first-principles calculations and available experimental data. With the present modeling, the phase transition temperatures, phase relations and properties of intermetallic precipitates can be predicted in order to plan heat treatments and rolling process for zirconium alloys. The phase contents of Zr-2.6Nb-0.03Fe and Zr-1.0Nb-1.8Fe (wt.%) versus temperature are presented as a practical example for application. Highlights: The enthalpies of intermetallic compounds were derived from VASP, which were applied in the thermodynamic assessment. The Zr-Fe system was reassessed, which treat the Fe23 Zr6 as a stable phase. The Fe-Nb system was revised to fit the experimental phase boundary of intermetallic C14 phase. The thermodynamic description of the Zr-Fe-Nb system was assessed, which can be used to plan heat treatments for Zr alloys.